Green human resource management practices and their impact on educational service quality- : An analytical exploratory study in private universities and colleges for the Holy Karbala Governorate - Abdul Hafedh Hussein, Hussein; Abbas Abed Hussain AL -janabey, Adel (Iraqi Journal for Administrative Sciences, 2024)
The current research aims to demonstrate the impact of green human resources management practices in achieving the quality of educational service within the research community represented by private universities and colleges in the Holy Karbala Governorate. The research sample was represented members and councils of universities and colleges researched. Their number is (120) members. In order achieve this, the independent variable was measured, green human resource management practices, as the dependent the main research problem, in order to reach the results of using the descriptive analytical approach and data collection through the questionnaire. The research relied on a set statistical methods based on programs ready-made (SPSSV.23AMOSV.23 Excel10). resource management and, and this indicates that the educational organizations examined are of great interest because of green human resource management that raises the best qualifications and capabilities.